2018
DOI: 10.1016/j.nedt.2018.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Development and psychometric testing of the nursing student mentors' competence instrument (MCI): A cross-sectional study

Abstract: The instrument exhibited acceptable psychometric properties, thereby proving itself a valuable tool for evaluating mentors' competence at mentoring students. Further assessments of its reliability, validity and generality for measuring mentor's competence for mentoring students in different contexts and cultures are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 21 publications
1
25
0
1
Order By: Relevance
“…In addition, we checked that the data met the following criteria for valid EFA: a Kaiser-Meyer-Olkin (KMO) statistic >0.60, indicating sample adequacy; a significance value of p<0.01, indicating sufficient relatedness of variables, according to Bartlett´s test of sphericity (Costello and Osborne, 2005); and item loadings exceeding 0.30 (DeVellis, 2011). In the previous study (Tuomikoski et al, 2018a), eight factors were found to have <5% variance and seven <4% variance. In order to identify constructs that explain more variance with fewer factors (Peterson, 2000), in this study we improved the EFA by stepwise removal of factors with low variance and relatively little consistency of theoretical association with nursing students' mentoring needs, according to international studies.…”
Section: Psychometric Testingmentioning
confidence: 83%
See 3 more Smart Citations
“…In addition, we checked that the data met the following criteria for valid EFA: a Kaiser-Meyer-Olkin (KMO) statistic >0.60, indicating sample adequacy; a significance value of p<0.01, indicating sufficient relatedness of variables, according to Bartlett´s test of sphericity (Costello and Osborne, 2005); and item loadings exceeding 0.30 (DeVellis, 2011). In the previous study (Tuomikoski et al, 2018a), eight factors were found to have <5% variance and seven <4% variance. In order to identify constructs that explain more variance with fewer factors (Peterson, 2000), in this study we improved the EFA by stepwise removal of factors with low variance and relatively little consistency of theoretical association with nursing students' mentoring needs, according to international studies.…”
Section: Psychometric Testingmentioning
confidence: 83%
“…Participants meeting two inclusion criteria (registered nurses working in a primary and/or specialized healthcare organization, with experience in mentoring nursing students during clinical practice) were recruited via a contact person provided by each organization. The questionnaire included questions on background information and the Mentors' Competence Instrument (Tuomikoski et al, 2018a). In the countries where data were collected electronically, two mixed approaches were used to improve the response rate.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the Mentors´ Competence Instrument (MCI) was developed and validated in the Finnish context (Tuomikoski et al, 2018b). The scale demonstrated good validity and reliability.…”
Section: Background and Literaturementioning
confidence: 99%